2021
DOI: 10.2147/opth.s333121
|View full text |Cite
|
Sign up to set email alerts
|

Profile and Management Outcomes of Fireworks-Related Eye Injuries in Saudi Arabia: A 16-Year Retrospective Study

Abstract: Background: Fireworks are a culturally significant part of celebrations in many parts of the world but can lead to blinding injuries. Objective: To decipher the profile and management outcomes of fireworks-related eye injuries at a tertiary eye hospital in central Saudi Arabia. Methods: This was a retrospective review of cases with fireworks-related eye injuries managed at our institution between 2003 and 2019. Demographic information, clinical features at presentation, mode of management, and visual outcome w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
1
10
1
Order By: Relevance
“…Furthermore, 62% of our patients were under the age of 30 years, which compares well to the 67% reported by Wisse et al [ 3 ]. The rate of bystander involvement varied in other countries from 39% in Saudi Arabia [ 15 ], 40–53% in the Netherlands [ 5 , 16 ], 56% in Germany [ 17 ], up to 64% in the United Kingdom [ 18 ], whereas in our study 51% of those injured were bystanders. However, missing information concerning the role played in the firework accident for 34% of our patients might represent a potential bias.…”
Section: Discussioncontrasting
confidence: 50%
“…Furthermore, 62% of our patients were under the age of 30 years, which compares well to the 67% reported by Wisse et al [ 3 ]. The rate of bystander involvement varied in other countries from 39% in Saudi Arabia [ 15 ], 40–53% in the Netherlands [ 5 , 16 ], 56% in Germany [ 17 ], up to 64% in the United Kingdom [ 18 ], whereas in our study 51% of those injured were bystanders. However, missing information concerning the role played in the firework accident for 34% of our patients might represent a potential bias.…”
Section: Discussioncontrasting
confidence: 50%
“…Generally, injuries caused by explosion involve significantly more binocular trauma (29.96% in the present study; 3.33–72.91% in previous reports [ 4 – 8 , 12 , 13 ]) compared with those related to ordinary causes (0–2.13%) [ 14 17 ]. The number of eyes involved seems to be related to the type and power of the explosives, for example, 3.33–16.32% for firework-related injuries [ 6 , 12 ] and 72.91% for injuries related to explosive military ammunition [ 13 ]. This explosive difference also leads to different types of MEI.…”
Section: Discussionmentioning
confidence: 99%
“…An explosive blast has sudden and devastating effects and usually causes great casualties [ 1 ]. Explosion-related eye injuries are a common cause of morbidities for survivors, whether the injury occurred during wartime, a disaster, or an explosion-related accident during peacetime [ 2 6 ]. Explosions rapidly generate impact waves with dramatic power, producing instantaneous peeling, implosion, and hemodynamic effects, and pressure differences (called primary or level I explosion injuries); fragments with high kinetic energy (leading to secondary or level II injuries); huge airflow capable of overturning the human body (leading to level III injuries); and hyperthermic or high-pressure chemical reaction (leading to level IV injuries) [ 4 , 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that that countries with stricter laws had 87% fewer ocular injuries than those with relaxed rules about the private use of fireworks 25 . Children are more likely than adults to sustain fireworks-related eye injuries 26 . Strict regulations concerning the use of fireworks are needed for a significant protective impact on the children since minors sustain a profound proportion of fireworks-inflicted severe injuries 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Children are more likely than adults to sustain fireworks-related eye injuries 26 . Strict regulations concerning the use of fireworks are needed for a significant protective impact on the children since minors sustain a profound proportion of fireworks-inflicted severe injuries 26 . Minors are undoubtedly placed at a greater risk for severe ocular trauma.…”
Section: Discussionmentioning
confidence: 99%